Fecal egg count of ascaris in relation to worm burden among treated subjects in Metro Manila - Balediata, Eva B.
The relationship between fecal egg count and worm load in Ascaris lumbricoids infection was determined from 94 cases in Metro Manila. Results showed a positive correlation between egg count and worm load. The egglaying capacity of the female Ascaris was estimated to be 786, 267 eggs per female per day in cases harboring 1-9 mature female worms and 583, 567 in cases harboring 10-35 mature females. The average female worm load per individual was 5.69. The proportion of unfertilized Ascaris eggs to the total number of Ascaris eggs was observed to be inversely related to the intensity of infection. Unfertilized eggs alone were found in very light and light infections. Fertilized eggs alone were seen in cases with very light, light and moderate infections. Mixed type of ova (fertilized and unfertilized) was observed in 100 of the heavily infected cases. The sex ratio of Ascaris lumbricoides was found to be 1:2.23 (M/F). No significant relation was found between sex ratio and intensity of infection.
Thesis (Master of Science in Public Health, Parasitology)--University of the Philippines Manila.
Keywords: Ascaris; Ascaris lumbricoides